Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1002/smll.202102543
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Electrical Conduction and Nanopore Formation During Controlled Breakdown

Abstract: ionic current therefore provides a simple single-molecule biosensing technique. [1][2][3][4] Indeed, over the past several decades, nanopores have proven to be versatile single-molecule sensing devices with applications ranging from DNA [5,6] and protein sequencing, [7,8] to ultra-dilute analyte detection, [9][10][11][12] polymer data storage, [13,14] and enzymology. [15] Nanopore sensors can be classified as either biological [16] or solid-state. [17] Biological nanopores generally consist of barrel shaped pr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 79 publications
1
13
0
Order By: Relevance
“…When the trans-membrane voltage reached 8 V or above, instantaneous breakdown events were observed, and the resulting pore size was larger than 15 nm. Previous studies have represented the mechanism of CDB as follows: (i) oxidation reactions of chloride ions (or reduction reactions of hydrogen ions) occur at the solution-membrane interface to supply (or remove) electrons; (ii) the electrons travel through charge traps in the SiN x membrane, which forms a highly conductive path and increases damage due to Joule heating [43,46,47]. Here, we measured the leakage current traces for the SiN x membrane before and after plasma treatment at a 600 mV applied voltage.…”
Section: Resultsmentioning
confidence: 99%
“…When the trans-membrane voltage reached 8 V or above, instantaneous breakdown events were observed, and the resulting pore size was larger than 15 nm. Previous studies have represented the mechanism of CDB as follows: (i) oxidation reactions of chloride ions (or reduction reactions of hydrogen ions) occur at the solution-membrane interface to supply (or remove) electrons; (ii) the electrons travel through charge traps in the SiN x membrane, which forms a highly conductive path and increases damage due to Joule heating [43,46,47]. Here, we measured the leakage current traces for the SiN x membrane before and after plasma treatment at a 600 mV applied voltage.…”
Section: Resultsmentioning
confidence: 99%
“…2. Following breakdown, reservoirs on both sides of the membrane were filled with 3.6 M LiCl, 10 mM Tris, and 0.1 mM EDTA at pH 8 solution and the device was left overnight for the ionic current through the nanopore to stabilise [50,65]. Following this, a linear ionic current as a function of the applied voltage was measured (S1.10 in the ESM).…”
Section: Biomolecular Sensingmentioning
confidence: 99%
“…Another technique that has been demonstrated relies on illuminating a plasmonic nanostructure with a laser during CBD. This results in nanopore formation at the center of the plasmonic hotspot [50]. To date, this is the only CBD method that has been used to integrate nanopores with on-chip nanostructures.…”
Section: Introductionmentioning
confidence: 99%
“…Note that, due to the asymmetry of this device geometry, the conduction and breakdown characteristics will change significantly depending on the direction of the applied electric field (as explained in Ref. 49 ). The results shown here were obtained by applying a negative voltage to the on-chip electrodes and grounding the electrolyte solution.…”
Section: Independent Fabrication Of Multiple Nanoporesmentioning
confidence: 99%
“…understood and may be the result of increased electron transfer processes at the membrane-electrolyte interface or increased electron transport across the dielectric 49 . Our results nonetheless indicated that it may be possible to confine nanopore formation to a specific region by locally heating the membrane.…”
Section: Self-aligning Nanopores With An On-chip Metal Nanoconstrictionmentioning
confidence: 99%